Caracterización y análisis de la actividad antigénica de proteínas de la membrana germinal de Echinococcus granulosus - Prieto, L.H. (2006)
Proteins present in an extract of Echinococcus granulosus germinal layer were separated in hydrophobic and hydrophilic phases using Triton X-114. The characterization carried out by sodium dodecyl sulphate polyacrylamide gel electrophoresis showed that proteins of apparent molecular weights of 102, 45, 28.5-28 and 15.5-15 kDa were present in the extract and in the aqueous phase (hydrophilic proteins). The immunological characterization of extract proteins performed by immunoblotting against to no immunized sheep serum, against to immunized with E. granulosus antigens sheep serum and against to anti-sheep immunoglobulin serum, showed similar reaction patterns. The dot immunobinding assay of extract proteins after Triton X-114 treatment against to human sera incubated in the presence of sodium dodecil sulphate ionic detergent, showed a positive reaction to cystic echinococcosis human sera. On the other hand, no reaction was observed to human sera without cystic echinococcosis and Mansonella ozzardi human infection serum.